Design of control algorithm over technical condition of hydrogen generators based on hydro-reactive compositions - Abramov, Yuriy; Borisenko, Vitaliy; Krivtsova, Valentina (Eastern-European Journal of Enterprise Technologies, 2017)
In order to describe the process of hydrogen generation, a system of differential equations is applied, which is matched with a transfer function of the hydrogen generator. A transfer function of the hydrogen generator is used for the transition to the frequency domain of research. We obtained an expression for the asymptotic logarithmic amplitude-frequency characteristic of the hydrogen generator. This characteristic is used to identify a simplified description of the hydrogen generator, which represents a model of dynamic link of the first order. Approximation error does not exceed 3.5 %. For such a model, we proposed a procedure for determining its parameter ‒ the time constant. The magnitude of time constant is determined using a test-impact, which represents a change in the area of the outlet of hydrogen generator in the form of a pulse of the semi-sinusoidal shape. In order to determine technical condition of the hydrogen generator, the test-impact is applied in the form of a change in the outlet in line with the harmonic law. The frequency of a test-impact is inversely proportional to the magnitude of time constant of the hydrogen generator. Based on the results of measurements of constant and variable pressure components in the cavity of a hydrogen generator, one determines a position of the figurative point relative to the assigned region on the frequency characteristic. Belonging of the figurative point to this region determines operational condition of the hydrogen generator.